2019
DOI: 10.1002/ajmg.a.61181
|View full text |Cite
|
Sign up to set email alerts
|

Cycloid Psychosis Comorbid with Prader–Willi Syndrome: A Case Series

Abstract: Psychosis is a relatively common psychiatric phenomenon seen in patients with Prader–Willi Syndrome (PWS). However, the presentation is atypical and difficult to classify within currently defined affective or psychotic disorders. This distinct presentation may be better understood as a phenomenon called “cycloid psychosis,” described as an episodic psychosis with rapid full recovery between episodes. This study retrospectively analyzed the cases of 12 patients with genetically confirmed PWS who presented to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Similar imaging studies have noted a reduction in SERT in the brain stem and other brain regions of adults with depressive illness vs healthy controls (Kambeitz and Howes, 2015). This is relevant to PWS given the greater prevalence of affective psychosis among UPD than DEL (Singh et al, 2019a). Finally, MTHFR TT polymorphism, which is the low activity polymorphism, was higher in mothers who had a child with Angelman syndrome due to a maternal imprinting defect, a deficiency of the methylation process, but data from fathers did not reach statistical significance (Zogel et al, 2006).…”
Section: Introductionsupporting
confidence: 53%
“…Similar imaging studies have noted a reduction in SERT in the brain stem and other brain regions of adults with depressive illness vs healthy controls (Kambeitz and Howes, 2015). This is relevant to PWS given the greater prevalence of affective psychosis among UPD than DEL (Singh et al, 2019a). Finally, MTHFR TT polymorphism, which is the low activity polymorphism, was higher in mothers who had a child with Angelman syndrome due to a maternal imprinting defect, a deficiency of the methylation process, but data from fathers did not reach statistical significance (Zogel et al, 2006).…”
Section: Introductionsupporting
confidence: 53%
“…A key pair of imprinting disorders that Crespi and Badcock (2008) cite in support of their hypothesis is Angelman syndrome—the paternally-biased condition characterized by sociability and ASD-like features—and Prader-Willi syndrome—the maternally-biased condition characterized by infantile undergrowth and, often, psychosis, commonly as part of atypical bipolar or schizoaffective disorder (Singh et al, 2019). Somewhat similarly, mutations in MECP2 lead to Rett syndrome in females and are typically lethal in males, but surviving males exhibit psychosis, usually as part of atypical BD, as well as impaired language development and pyramidal/parkinsonian signs (termed PPMX syndrome, OMIM 300055) (Lambert et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that rates of significant mood lability and affective mood disorders including major depression and bipolar disorder in PWS are increased in the mUPD subtype [68]. Most notable, however, is that the mUPD genetic subtype also has a strikingly higher prevalence of psychosis, including a phenomenon referred to as "cycloid psychosis" [87], with an estimated lifetime prevalence for psychosis of greater than 60%, compared with the deletion subtype that has a similar prevalence to adults with intellectual disabilities in the general population, which ranges from about 2.6 to 4.4% [88].…”
Section: Prader-willi Syndromementioning
confidence: 99%